Standardization of Wedge Grafting Technique in Guava (Psidium guajava L.) under Subtropical Conditions of Himachal Pradesh - Banyal, Ajay Kumar; Guleria, Tarun; Banyal, Sanjeev Kumar; Thakur, Asha; Pathania, Sunita (International Journal of Bio-resource and Stress Management, 2022)
The present investigation was carried out in the fruit nursery, Department of Fruit Science, College of Horticulture and Forestry, Neri, Hamirpur, Himachal Pradesh w.e.f., June, 2019−July, 2020. In the present investigation two factors viz., time of wedge grafting (mid-June, mid-July, mid-August, mid-September, mid-February and mid-March) and use of polycap (Graft union covered with polycap or without polycap) were studied to standardize the ideal time for wedge grafting with or without the use of polycap under protected conditions. Wedge grafting is being used as a rapid and successful technique for year-round production of guava plants, even in harsh climatic conditions and coving the graft union with polycap has also been used for obtaining higher success due to the development of a congenial microclimate in the graft’s region. The results thus obtained showed that wedge grafting performed in guava during mid-February covered with polycap resulted in maximum graft-take (84.44%) and survival percent (80.31%). Whereas, wedge grafting executed during mid-July and covered with polycap resulted in maximum bud sprout (71.11%), minimum time for bud sprouting (10.67 days) and first leaf emergence (14.24 days). Wedge grafts performed in mid-July, covered with polycap also induced a notable increase in plant growth attributes in guava plants viz., production of number of leaves and sprout length at 30, 45, 60, 75 and 90 days after grafting.